Immobilization of epoxy molding compound heavy metals by hydration and clinkerization through the process of stabilization/solidification and co-processing - Ramirez, Ninette Pajarillaga (2007)
This study was undertaken to develop information on the fate of heavy metals in Epoxy Molding Compound (EMC), in stabilization/solidification (S/S) process and as an alternative fuel and raw materials (AFR) in cement manufacturing process. Such information was necessary to evaluate changes in the heavy metals availability to evaluate whether environment or product quality impact could be expected. This study seeks to determine the potential for reachability on a metal-by metal basis under different pH conditions. In S/S, theoretical calculations and actual analysis of stabilized/solidified EMC were analyzed under baseline conditions and while the EMC was used as an aggregate substitute. Test results indicate that, although pH was an important factor in determining metal fate, other processes such as metal specialization might influence the degree of metals immobilization. In co-processing, particular attention was paid to metal fate introduced with the raw feed or with the fuel. A kiln in a local cement manufacturing facility were analyzed by taking samples of all material input and output including raw feed, fuel, clinker, and kiln dust. Multiple sets of data were taken both under baseline conditions and while the kiln was co-processing EMC. Test results indicate that, although relative volatility was an important factor in determining metal fate, other processes such as development of recirculating loads might affect the degree of incorporation of the metals in the clinker. The metals tested were As, Cd, Co, Cr, Cu, Hg, Mn, Ni, Pb, Sb, Tl, V, and Zn.